Home sanitation - McLaren, Nettie (My University, 1900)
Introduction: Domestic sanitation embraces a large province of possibility and responsibility. Within its jurisdiction come many of the little things which have so much to do in determining many fates. In all classes of society, except those which are degraded and ignorant, we find a growing interest in guarding against unhealthful conditions of person, house and environment. Intelligent people do not now attribute the consequences of our neglect and carelessness to the “Affective dispensations of Providence,” as many did in olden times. The interest in sanitation is growing. As a people, we live in more comfortable houses than are found in any other country in the world. But if still more interest should be taken in the subject there would be much less sickness. To insure health, we must have fresh air, pure water, wholesome food, clean houses, clean streets, good drainage, proper clothing and cleanly habits.
Citation: McLaren, Nettie. Home sanitation. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Home Economics; Sanitation; Theses; Manuscripts (documents)